Motivational and Cognitive Aspects of Formation of Teachers' Professional Readiness for Professional Activities in Inclusive Education - L.A. Guterman; L.V. Goryunova (Moscow State University of Psychology and Education, 2023)
The relevance of the study is the need to improve the quality of formation of teaching inclusive education. The purpose of the study was to identify an assessment of the motivational-cognitive aspect of the readiness of future teachers to work in inclusive environment comparing with their level of readiness. The materials of empirical research are obtained from a sample of 5th year students of “Pedagogical Education” at the Southern Federal University (N=104) and teachers in the city of Rostov-on-Don and the Rostov region (N=12739). The leading research method is analysis of the results of a survey of university students and schoolteachers. The results of the study showed that the average level of readiness for inclusive education prevails among respondents. The results of the study make it possible to say that the leading criterion for teachers’ readiness is motivational and cognitive, with skillful knowledge of humanitarian and assistive technologies for working with persons with disabilities. The materials of the article are of practical value for the design of teacher training programs in higher and additional professional education